Upaya hukum dalam penyelesaian kontrak bisnis di Indonesia - Fadlan, Mochamad Lailul (Maliki Interdisciplinary Journal, 2023)
The purpose of this study is to determine the choice of law in conflict resolution. The research method uses a normative juridical research type, with a statutory approach. The results of the discussion show that in completing contract settlements, there are 2 types of legal options, namely litigation and non-litigation. Litigation legal efforts are efforts that can be made by the disputing parties through the courts. Meanwhile, what is meant by non-litigation legal remedies are legal efforts that can be made outside the court. Non-litigation legal remedies are regulated in Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. Article 1 Paragraph (10) of the Law explains that there are several legal remedies that can be made outside the court, namely consultation, negotiation, mediation, conciliation, and arbitration or expert judgment. Litigation legal efforts will provide legal certainty because they are binding and have the nature of a win-lose solution. Meanwhile, non-litigation legal remedies will be more efficient in terms of time and cost, maintain the confidentiality of the parties, and are a win-win solution.